Implementation of Religious Values in Arabic Grammar for Madrasah Aliyah Students (A Case Study at MA Sa'id Yusuf) - Abdurahman, Abdurahman; Zulfiqri, Muammar (Cerdika: Jurnal Ilmiah Indonesia, 2025)
This research aims to analyze the implementation of religious values in Arabic grammar among students at MA Sa'id Yusuf Depok, focusing on how students learn and apply religious values in the practice of wudhu (ablution). The research adopts a qualitative approach, using data collection techniques such as participatory observation, interviews, and document analysis. The results indicate that MA Sa'id Yusuf has successfully created a learning environment that integrates religious values with Arabic grammar, ensuring that students not only learn grammar but also understand its spiritual significance. The implementation of religious values is reflected in the students' awareness of heart purity, as they are taught to maintain sincere intentions, cultivate positive social attitudes, and avoid arrogance, self-admiration, and other negative traits. The findings of this research can contribute to the development of Arabic language materials, offering valuable guidance for Islamic educators to strengthen the integration of religious values in language learning. The practical implication of this research is that involving students in religious activities from an early age helps shape their character and provides a strong foundation for their religious and social lives throughout their lifetime, promoting not only academic success but also the development of moral and spiritual values.